2017
DOI: 10.1038/s41598-017-10841-w
|View full text |Cite
|
Sign up to set email alerts
|

Disorder versus two transport lifetimes in a strongly correlated electron liquid

Abstract: We report on angle-dependent measurements of the sheet resistances and Hall coefficients of electron liquids in SmTiO3/SrTiO3/SmTiO3 quantum well structures, which were grown by molecular beam epitaxy on (001) DyScO3. We compare their transport properties with those of similar structures grown on LSAT [(La0.3Sr0.7)(Al0.65Ta0.35)O3]. On DyScO3, planar defects normal to the quantum wells lead to a strong in-plane anisotropy in the transport properties. This allows for quantifying the role of defects in transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In the cuprates, the 0-K divergence in scattering rates has been explained with anisotropies in the elastic scattering rates [71]. In a recent study of SmTiO 3 / SrTiO 3 /SmTiO 3 quantum wells, we showed that disorder affected the residuals in both the Hall angle and longitudinal resistances, but it did not affect their 0-K divergence [70].…”
Section: Hall Mobility or Hall Anglementioning
confidence: 77%
See 1 more Smart Citation
“…In the cuprates, the 0-K divergence in scattering rates has been explained with anisotropies in the elastic scattering rates [71]. In a recent study of SmTiO 3 / SrTiO 3 /SmTiO 3 quantum wells, we showed that disorder affected the residuals in both the Hall angle and longitudinal resistances, but it did not affect their 0-K divergence [70].…”
Section: Hall Mobility or Hall Anglementioning
confidence: 77%
“…The resistance is ~ T 5/3 above ~100 K, while the Hall angle is always ~ T 2 [69]. Lifetime separation was also investigated in quantum wells of SrTiO 3 [57,70], such as formed in SmTiO 3 /SrTiO 3 / SmTiO 3 heterostructures, which contain mobile charge densities on order of 7 × 10 14 cm −2 and which exhibit numerous correlated phenomena, such as itinerant magnetism and pseudo gaps, when their thicknesses are reduced to a few atomic planes. These studies showed that the lifetime separation can have two components, namely the different temperature dependencies of Hall angle and longitudinal resistances, as seen in figure 4, but also a divergence in their 0-K residuals [57].…”
Section: Hall Mobility or Hall Anglementioning
confidence: 99%
“…Recently, trace gas sensors based on tunable diode laser absorption spectroscopy (TDLAS) are widely used due to their high detection sensitivity and selectivity as well as fast response time, which permits online monitoring of target gas concentrations 710 . The basic principle of tunable diode laser absorption spectroscopy can be described briefly as: (a) The emission wavelength of diode laser, is tuned over the characteristic absorption lines of a target gas; (b) Then, the gas concentration can be determined through the reduction of the measured signal intensity caused by gas absorption 11 .…”
Section: Introductionmentioning
confidence: 99%